A comparative study of propofol, thiopentone sodium, and ketofol as induction agents for electro convulsive therapy - Nagraju R Gaddam; Vasanti P Kelkar (Sasturkar); Sanhita J Kulkarni; Pradnya S Joshi; Pramod V Bhale (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: Thiopentone and propofol are most commonly used induction agents for electro convulsive therapy (ECT). Recently, ketofol, an admixture of propofol and ketamine, is being tried in ECT. We aimed to compare propofol, thiopentone, and ketofol as induction agents during ECT regarding their effects on ECT-induced hemodynamic changes, seizure duration and recovery parameters. Material and Methods: This prospective randomized double blind study was conducted in 30 patients between 18 and 65 years with ASA status I and II scheduled for ECT. All patients received all study agents for first three sessions of ECT. The observations were compiled as Group K (Inj. Ketofol i.e., Inj. propofol 0.5mg/kg + Inj. ketamine 0.5mg/kg), Group P (Inj. propofol 1mg/kg), and Group T (Inj. thiopentone 3mg/kg).Heart rate (HR) and blood pressure (systolic, diastolic, and mean) was recorded at pre op, 0, 5, 10, and 20 min after ECT. The seizure duration, time to spontaneous eye opening, andobeying verbal commands and agitation score were recorded. Results: Statistically significant difference was seen in HR at 10 min after delivery of shock; in systolic BP at 2 min after shock; in diastolic BP after administration of study drug and immediately after shock and in mean arterial pressure at post induction, 0and2 min after shock with group T showing higher values compared to group K and P (p < 0.05). At all other times HR andBP was comparable in all the three groups.Seizure duration was more in group T than Groups P and K although the difference was statistically insignificant.Time to spontaneous eye opening and obey verbal commands was comparable in all groups.Mean agitation score was highest in group T than Groups P& Kwith Group P showing least value (p = 0.003). Conclusion: Propofol and ketofol showed superior hemodynamic stability than thiopentone but comparable seizure duration and recovery parameters. Thus, propofol and ketofol can be effectively used as induction agents for ECT although propofol is associated with lesser agitation than ketofol.